An Online Cross-Sectional Study of Nursing Students' Perceptions of Workplace Incivility in Nursing Schools During the COVID-19 Pandemic - Majd T. Mrayyan PhD, MSc, BSc; Abdullah Algunmeeyn PhD, MSc, BSc; Hamza Yousef Abunab PhD, MSc, BSc (SAGE Publishing, 2024)
Introduction Despite a growing body of evidence on academic incivility, limited information exists on workplace incivility perceived by nursing students in nursing schools. This study, conducted amid the COVID-19 pandemic, explores nursing students' perceptions of workplace incivility in Jordanian nursing schools and investigates demographic-based differences. Methods This study employed a descriptive cross-sectional design, using an online survey for data collection. A convenience sample of 104 nursing students from diverse backgrounds and various Jordanian universities participated, allowing for a comprehensive examination of workplace incivility perceptions at a specific point in time. The online survey ensured efficient data collection, enhancing accessibility and ease of participation. This approach aimed to capture a snapshot of nursing students' perspectives on workplace incivility within a given time frame and across multiple educational institutions, efficiently gathering data from a geographically dispersed and demographically varied sample. Results Students perceived workplace incivility in nursing schools as "mild," with moderate confidence in schools' ability to address it. Workplace civility was rated between 60.00% and 70.00% on a 0-100 scale. The overall mean for uncivil behaviors was "sometimes," with criticism of expertise as the most common. Incivility in the past year was seen as "rare," with misusing authority being the most frequent. Male and low-GPA students reported higher perceptions of incivility. Stress was the most perceived contributing factor, and a lack of administrative support was the main barrier. Establishing codes of conduct was considered the key strategy for fostering workplace civility. Conclusion Workplace civility is prevalent in Jordanian nursing schools, even amid the COVID-19 pandemic. However, the occasional occurrence of incivility behaviors should be approached with caution. To enhance perceptions of workplace civility, nursing schools should prioritize effective teaching, a friendly environment, and respectful relationships. Encouraging faculty members to reassess their performance, starting with identifying academic workplace incivility, is crucial.